Pendidikan Inklusi Untuk Anak Berkebutuhan Khusus pada Penyandang Attention Deficit Hyperactivity Disorder (ADHD) - Nurfadhillah, Septy; Fauziah, Nur Sella; Mulyani, Tyasti Sri; Priangle, Syafira; Oktadia, Dwi Putri Nur; Prasetya, Chintya Eka; Rosiana, Melya; Madhofi, Faraditha (Lembaga Yasin AlSys, 2022)
ADHD is a neurodevelopmental disorder in which a child presents a significant problem due to a lack of attention or hyperactivity-impulsivity. ADHD can interfere with the development of children in terms of cognitive, behavioral, socialization and communication. A common mistake that ADHD treatment through pharmacological therapy will eliminate all the symptoms of hyperactivity and impulsive problems in children with ADHD, but the use of ADHD drugs in the long term then it will affect the children. Another alternative for dealing with ADHD children using a counseling approach is behavioral cognitive behavioral approach and Adlerian play therapy.Understanding of behavioral cognitive approaches and Adlerian play therapy can help address early childhood problems especially those with ADHD disorders.